Single-Step Synthesis of Highly Sensitive 19F MRI Tracers by Gradient Copolymerization-Induced Self-Assembly - Panakkal, Vyshakh M.; Havlicek, Dominik; Pavlova, Ewa; Jirakova, Klara; Jirak, Daniel; Sedlacek, Ondrej (Biomacromolecules, 2024)
Amphiphilic gradient copolymers are promising alternatives to block copolymers for self-assembled nanomaterials due to their straightforward synthesis via statistical copolymerization of monomers with different reactivities and hydrophilicity. By carefully selecting monomers, nanoparticles can be synthesized in a single step through gradient copolymerization-induced self-assembly (gPISA). We synthesized highly sensitive 19F MRI nanotracers via aqueous dispersion gPISA of hydrophilic poly(ethylene glycol) methyl ether methacrylate (PEGMA) with core-forming N,N-(2,2,2-trifluoroethyl)acrylamide (TFEAM). The PPEGMA-grad-PTFEAM nanoparticles were optimized to achieve spherical morphology and exceptional 19F MRI performance. Noncytotoxicity was confirmed in Panc-1 cells. In vitro 19F MR relaxometry and imaging demonstrated their diagnostic imaging potential. Notably, these gradient copolymer nanotracers outperformed block copolymer analogs in 19F MRI performance due to their gradient architecture, enhancing 19F relaxivity. The synthetic versatility and superior 19F MRI performance of gradient copolymers highlight their potential in advanced diagnostic imaging applications.